Gradiente de umidade na maturação de sementes de milho doce e sua qualidade fisiológica - Perretto, Élcio Luiz (2012)
The aim of this study was to identify the ideal sweet corn seed harvest moment by different determinations like moisture gradient in each harvest, moisture content, seeds dry matter, Hot Unity and physiological quality. Four genotypes of sweet corn, carrier of gene shrunken 2 (sh2) and nominated super sweet was used in this study. Ears from plants in the same development stage were collected. Seed harvest for the first genotype began 39 days after the flowering at intervals of two days until to complete eight harvest periods. Morphological determinations evaluated were moisture gradient between the seeds in each harvest, moisture content, seeds dry matter and Hot Unity. Seeds physiological quality was evaluated by germination test, first count of germination, soil emergence and cold test, without soil. Based on the results, the conclusions are: 1) the ideal moment to harvest sweet corn was with seed moisture content between 40 and 60% depending on genotype; 2) the ideal period to harvest the seed of sweet corn varies among genotypes; 3) the Hot Unity between 2007 to 2160°C relates to the best times to harvest the genotypes of sweet corn; 4) the moisture gradient of the seeds in a ear of sweet corn can reach more than 40 percentage points; 5) the seed moisture loss on the ear reaches around 1.5 percentage points per day after 40 days of flowering.